The Implementation of Culturally Responsive Teaching to Improve Students' Learning Outcomes and Activity - Rahayu, Binti Nuriyati; Muchlis, Muchlis; Mumpuni, Ariwati Wahyu (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
This study aims to determine the increase in students’ learning outcomes and activity through the implementation of Culturally Responsive Teaching (CRT) to solubility and solubility product material in Class XI-MIPA G SMAN 1 Kediri. This research was conducted using the classroom action research model developed by Kemmis and Taggart which consisted of plan, action, observe, and reflect in two cycles. The data obtained was in the form of quantitative data, namely learning outcomes and qualitative data, namely observation sheets. Quantitative data analysis was carried out using descriptive statistical techniques with percentage formulas and descriptions for qualitative data. In the pre-action, students’ learning outcomes and activity were obtained with a mean of 57.2 and 63.8. In Cycle I, students’ learning outcomes increased by an average of 80.0 and students’ activity increased by an average of 71.4, while students’ learning outcomes increased by 89.1 and students’ activity increased by 91.4 in Cycle II. The results showed that the implementation of CRT can improve students’ learning outcomes and activity in Class XI-MIPA G SMAN 1 Kediri.